Structural and Functional Effect of Impaired Iodine Supply on the Thyroid Gland, Ovaries and Thymus - Bahram J. Mahmoudi, Reza G. Yasmin, Cyrus J. Parinaz (Academic Journal of Clinicians, 2025)
Formation and regulation of thyroid metabolism is a topical issue in biology and medicine. The functional orientation of the thyroid gland changes under the influence of environmental pollution, deterioration of social conditions and diet, increased stress, allergization and immunization of the population. In this regard, thyroid pathology is currently becoming increasingly environmentally and socially conditioned. Dynamic structural and functional reactions of the thyroid gland are aimed at stopping the unfavorable factor, but compensatory reserves for maintaining homeostasis are not unlimited. The problem of iodine intake disorders is relevant for many regions globally. The existing clinical and morphological data convince us of the necessity of complex clinical and experimental studies. Ovarian insufficiency is often caused by dysfunction of the thyroid gland, however, the morphological aspects of the disturbance of interrelated processes in the thyroid gland and ovaries are practically unknown. It is extremely difficult to obtain morphological verification in the clinic of a pathological process developing according to a complex scheme of mutual aggravation, with the involvement of interrelated organs and systems, with the imposition of drug pathomorphosis. Few works are devoted to the structural basis of the influence of the thyroid systems of the mother and offspring in the presence of thyroid dysfunction in pregnant women